Income and community service are the two most important factors in increasing motivation to teach equality tutors (Study on equality education program) - Karnadi, Luh Putu Arsih; Agung, Anak Agung Gede; Dantes, Kadek Rihendra; Purnamawati, I Gusti Ayu (Edelweiss Applied Science and Technology, 2025)
This study aims to explain the factors that affect the motivation of tutors to teach at PKBM Widya Sentana. The teaching and learning process at PKBM is carried out by tutors as educators. The importance of tutoring has not received much attention from the government, especially regarding professional careers. However, the lack of attention does not reduce the motivation of tutors to teach at PKBM. The research used a qualitative type with a phenomenological study approach. Data was obtained through in-depth interviews and analyzed through a reduction process, data display, and data verification. Based on the findings, there are two important factors in increasing tutors’ motivation to teach. The first factor is community service, which refers to internal encouragement; tutors teach with the aim of contributing to educating people’s lives. The second factor is income, related to external encouragement; in teaching, tutors are given rewards according to their work performance. These two factors are interrelated and support the motivation of equality tutors to play a role in community-based, non-formal educational institutions. The results of this study can add insight into the role of equality education institutions in educating people’s lives and can serve as a reference for relevant research in the future.